2018
DOI: 10.1080/03075079.2018.1496412
|View full text |Cite
|
Sign up to set email alerts
|

Research skills that men and women developed at university and then used in workplaces

Abstract: This qualitative study probed the mismatch between graduates' and employers' perspectives, especially in regard to graduates' learning orientation and investigating skills. Specifically, the study delved into male and female graduates' perceptions of research skills that were developed explicitly during their undergraduate degree and used by them in employment for research, investigations and for ongoing learning that kept them current. Thematic analysis of the qualitative data revealed substantial similaritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
2
22
0
2
Order By: Relevance
“…What about our learning is distinctively sapiens? We have big brains, proportionally, but Neanderthals had a bigger brain volume [33] and still died out. As noted early in this chapter, Homo sapiens have been very efficient at solving problems whose solutions created new problems which emerged days, years or centuries later.…”
Section: Billion Brains: Learning From Human Prehistory To Contemmentioning
confidence: 99%
See 1 more Smart Citation
“…What about our learning is distinctively sapiens? We have big brains, proportionally, but Neanderthals had a bigger brain volume [33] and still died out. As noted early in this chapter, Homo sapiens have been very efficient at solving problems whose solutions created new problems which emerged days, years or centuries later.…”
Section: Billion Brains: Learning From Human Prehistory To Contemmentioning
confidence: 99%
“…Of the many MELT, only three have undergone some long-term evaluation-the RSD [31][32][33], OPS [34] and the WSD [35,36]. Conceptual frameworks cannot be effectively evaluated through any one trial because ways of interpreting and implementing a conceptual framework vary markedly.…”
Section: Trusting the Melt?mentioning
confidence: 99%
“…This framework arranged systematically to highlight and to facilitate the development of college students in carrying out research. Many skills related to HOTs can be trained by this framework, for instance, problem-solving skill and critical thinking skill, discipline-specific research skill and a capacity of lifelong learning (Ain, 2019;Willison, 2016).…”
Section: The Rsd Frameworkmentioning
confidence: 99%
“…However, it was also found that there was a risk that the thinking skills developed may atrophy. A follow-up series of studies looked at the explicit use of MELT across multiple semesters of a degree in Media [3,4], Oral Health [5] and Animal Science [6].…”
Section: Undergraduatementioning
confidence: 99%